Political economy of climate change: Key measures to tackle the challenge - Sharma, S.L. (Economic and Political Weekly)
The major causes of climate, a comparative appraisal of the two perspectives$1 (Bglobal North and South$1 (Bbeyond them and a third perspective is advanced that traces the cause of climate change to the flawed vision of development.- Reproduced s